PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN KUIS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN KELAS VI DI UPTD SDN 190 BARRU - Reza Azwar; Sahria; Sri Rahayu (STKIP Subang, 2024)
This research was motivated by the low mathematics learning outcomes of grade VI students of UPTD SDN 190 Barru on fractional materials, where 67% of students have not reached the Minimum Negligence Criteria (KKM) set at 75. The purpose of this study is to improve students' mathematics learning outcomes through the application of the Problem Based Learning (PBL) model assisted by quizzes. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. The subjects of the study were 12 grade VI students. The results showed a significant improvement in student learning outcomes from cycle I to cycle II, with classical completeness increasing from 60% to 88%. The PBL model assisted by quizzes has been proven to be effective in improving students' understanding of concepts and learning outcomes on fractional materials